Does video assistant referee technology change the magnitude and direction of home advantages and referee bias? A proof-of-concept study - Isin, A.; Yi, Q. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Background This study analyzed how Video Assistant Referee (VAR), introduced to improve the accuracy of referee decisions in football, changes the magnitude and direction of home advantage and referee bias in the Turkish Super League.